Characterization of the inflammatory features of central centrifugal cicatricial alopecia. (6th March 2020) - Flamm, Alexandra; Moshiri, Ata S.; Roche, Fritzlaine; Onyekaba, Ginikanwa; Nguyen, Jennifer; James, Alaina J.; Taylor, Susan; Seykora, John T.
Abstract: Central centrifugal cicatricial alopecia (CCCA) is a scarring alopecia that primarily affects women of African descent. Although histopathological features of CCCA have been described, the pathophysiology of this disease remains unclear. To better understand the components of CCCA pathophysiology, we evaluated the composition of the inflammatory infiltrate, the distribution of Langerhans cells (LCs), and the relationship between fibrosis and perifollicular vessel distribution. Our data indicate that CCCA is associated with a CD4‐predominant T‐cell infiltrate with increased LCs extending into the lower hair follicle. Fibroplasia associated with follicular scarring displaces blood vessels away from the outer root sheath epithelium. These data indicate that CCCA is an inflammatory scarring alopecia with unique pathophysiologic features that differentiate it from other lymphocytic scarring processes.